Twelve-month recovery of medical decision-making capacity following traumatic brain injury. (6th September 2016) - Steward, Kayla A.; Gerstenecker, Adam; Triebel, Kristen L.; Kennedy, Richard; Novack, Thomas A.; Dreer, Laura E.; Marson, Daniel C.
Abstract : Objective: To investigate recovery of medical decision-making capacity (MDC) over the first year following traumatic brain injury (TBI). Methods: A total of 177 participants (111 persons with TBI and 66 healthy controls) were recruited from an inpatient/outpatient TBI rehabilitation unit and outpatient neurology department. Participants with TBI were classified by injury severity into subgroups: mild TBI (mTBI; n = 28), complicated mild TBI (cmTBI; n = 23), and moderate/severe TBI (msevTBI; n = 60). Control and TBI groups were compared at 1 month (t1), 6 months (t2), and 12 months (t3) postinjury using the Capacity to Consent to Treatment Instrument (CCTI), which evaluates MDC using 5 consent standards: expressing choice, reasonable choice, appreciation, reasoning, and understanding. Results: Relative to controls, no TBI group displayed impairment on CCTI expressing choice or reasonable choice at any timepoint. Those with mTBI had reduced appreciation and understanding at t1, which resolved by t2. The cmTBI and msevTBI groups were impaired on all 3 complex consent standards at t1. While patients with cmTBI improved to a level similar to controls by t3, those with msevTBI remained impaired on reasoning and understanding. Across all TBI groups, notable MDC improvement only occurred over the first 6 months postinjury. Conclusions: Over 1 year, most individuals with mTBI or cmTBI regain MDC, while many individuals with msevTBI have lingering deficits in reasoning and comprehension of treatment information. Clinical recovery of MDC occurs primarily during the first 6 months post-TBI regardless of injury severity. Clinicians can therefore identify MDC outcomes in TBI at 6 months postinjury.